On the previous note in this series we learnt / revised that
a∑n=2(n+a)(n+a−1)−2a2−a
That's the formula when the difference (d) is 1 so what would the formula be if d=1
Let's denote the whole thing as a∑nd
So let's say that a=3, n=6 and d=2 what equation would we get from that.
3∑62=3+5+7+9+11+13=48
We're going to have to use a different method to last time to solve this.
Since a=3 and d=2 we can put those in to get
a∑6d=a+(a+d)+(a+2d)+(a+3d)+(a+4d)+(a+5d)
That can be written as
a∑6d=6a+(1+2+3+4+5)d
a∑nd=na+2dn(n−1)
This is basically a simplified version of the previous equation with a d added in to account for the difference. This formula however is still flawed as it can only handle a constant variable for d.
#Algebra
#Finiteseries
#SummationOfSeries
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.